Plutarch's Cosmological Ethics. - DEMULDER, BRAM (Book collections on Project MUSE., 2022)
Plutarch of Chaeronea (c. 45-120 CE) is the most prolific and influential moral philosopher in the Platonic tradition. This book is a fundamental reappraisal of Plutarch?s ethical thought. It shows how Plutarch based his ethics on his particular interpretation of Plato?s cosmology: our quest for the good life should start by considering the good cosmos in which we live. The practical consequences of this cosmological foundation permeate various domains of Greco-Roman life: the musician, the organiser of a drinking party, and the politician should all be guided by cosmology. After exploring these domains, this book offers in-depth interpretations of two works which can only be fully understood by paying attention to cosmological aspects: 'Dialogue on Love' and 'On Tranquillity of Mind'.